Moderasi Bertasawuf Perpektif Abdul Halim Mahmud - Isgandi, Yiyin; Yiyin Isgandi, Yiyin (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2023)
Sufi muslims are divided into two extreme groups, there are; 1) ultra-conservative sufi as right extreme, and 2) liberalist sufi as left extreme. The ultra-conservative sufi are those who are fanatical toward mursyid teachers, teaching process, blame other teacher, and sufism order without proper explanation or do tasawuf only for wordly material interest. Meanwhile, the liberalists sufi who are free to interpret religious teachings according to their own thinking logically, or who regard themselves as prophets who receive revelation or even claim to be God. This study aims to explore the form of Abdul Halim Mahmud’s moderation of tasawuf and its typology. This study categorized as qualitative library research that uses an analytical descriptive approach. In short, the result finding showed that Mahmud’s moderation of tasawuf includes three elements which interwinned and continued from the begining of the journey to the end; knowledge, mujahadah, and worship. Furthermore, Mahmud’s form moderation of tasawuf suggested that; 1) to follow the messenger of Allah and guided by the Al-Qur’an and Sunnah as always, 2) to mediate two extreme sufi groups in wise ways, 3) to tolerance intra and inter-religious with a rational reinterpretation the concept of sufism based on Islamic law, and 4) to avoid violence by instilling the teachings of love and pleasure as well as supporting the true goverment programs and acomodating the local culture. In the last finding, Mahmud’s moderation of tasawuf also included in catagory of moral, practicing, and philosopical tasawuf models at the same time.